Didactic-pedagogical prescriptions for physical education in the periodical press of teaching and techniques (1932-1960) - Lucas Oliveira Rodrigues de Carvalho; Juliana Martins Cassani; Amarílio Ferreira Neto; Wagner dos Santos (Journal of Physical Education (Maringá), 2020)
The objective of the study was to analyze the articles published by the periodical press of education and techniques (19321960), whose purpose was to prescribe the teaching of Physical Education. It has, as a source, the Revista de Educação Física and Revista Educação Physica, and uses, as theoretical and methodological assumptions, studies on the analysis of printed matter. The results indicate that, within the sources, there were similar ways of prescribing the teaching of Physical Education. In that, as it is inserted and consolidated in school curricula, it has also been elaborated ways of signifying it, with the teaching role as the central place to strengthen its schooling project. The publication of didactic-pedagogical prescriptions evidenced the contributions of different groups of writers and institutions to systematize a new discipline centered on the nature and specificity of their knowledge, offering the necessary subsidies for their stay in school. These printed consisted of devices of didactic-pedagogical use, collaborating with the formation of the teachers that would act with the teaching of Physical Education in the school.